Redakcinė kolegija ir turinys - Šarkiūnaitė, Ingrida (Vilnius University Open Series, 2019)
In keeping with the scholarly traditions of Vilnius University Kaunas Faculty, the 14th “Prof. Vladas Gronskas International Scientific Conference” was held in December 2019. This international conference is an arena for cooperation and scholarly fellowship, with young researchers, master and doctoral students from Lithuania as well as Latvia, Ukraine, India, Bulgaria, Hungary, Turkey, Russia, Israel, Nigeria participating in the different conference sections and poster session. The main goal of this scientific gathering has always been to contribute to the reliable, safe, effective and sustainable economy and business development. Thus, the organizing committee strives to create a suitable platform for well‐grounded and open discussion where young researchers have the opportunity to present and share their insights. Encouraging entrepreneurship is a crucial condition for economic growth and this puts forward a new approach to business, creativity, value creation, and the implementation of innovations. It is precisely in this context where business and science should interact. To reinforce this relevant bond, the guest speakers of the plenary session were selected amongst experienced practitioners and scholars. This conference encourages internationalization and a closer cooperation between science and business. In 2019, the conference is going to expand the range of themes and invite not only the young but also experienced scientists to present their scientific findings. Hopefully, there has been some useful take‐away for both academia and business conference participants: new insights and inspirations for further scientific research and possible solutions to boost Lithuanian economy. On behalf of the Scientific Committee Assoc. Prof. Dr Ingrida Šarkiūnaitė